Cation xanthated exchangers from colombian sub-bituminous coals effectively removed cadmium and lead from aqueous solutions - Gómez de Arco, Lewis; Alzate Rodríguez, Liliana; Colpas Castillo, Fredy; Fernández Maestre, Roberto (Universidad Autónoma de Nuevo León, 2011)
In Colombia, low rank coals are almost totally used for power and matallurgical aims, which are activities that produce contamination. In this investigation, as an alternative to the traditional use of low rank coals, we prepared cationic xanthated exchangers from a subbituminous coal (67.6%C, 4.6%H, 22.4%O, 0.6%S, 3.2% ashes and 46.2% volatile matter) of Montelíbano-Córdoba; this exchanger showed better exchange capacities for cadmium and lead (1.8 meq/g) than traditional sulphonated exchangers (0.56 and 1.11 meq/g for cadmium and lead respectively). Xanthation was verified at 30ºC and at 5-10ºC with NaOH and CS2. The best performance of xanthation, determined by Infrared spectrometry and ion exchange experiments, ocurred at low temperatures maybe due to CS2 volatility. By diminishing the particle size of coal the exchange capacity increased. The exchange capacity was evaluated by flame atomic absorption spectrometry.